Apropriação da dimensão técnico-operativa dos assistentes sociais : condição para a construção de competência profissional - Araújo, Eliane Julkovski de (2013)
This dissertation aims to identify how social workers have been articulating the technical-operative dimension along with the ethical-political and theoreticalmethodological dimensions into their daily work. To launch light over the subject of this research we took as basis the critical perspective of Marxist dialectics and we elected as subjects to be researched the social workers active at the CRAS of Cuiaba, graduated after the year of 2000, in universities that are necessarily face-to-face and that have at least one year of professional experience. We identify through the analysis of the statements of these professionals that even today, after a review of the Social Work course curriculum and the new guidelines assumed after 1996, there's fragility in the formation process and in the forms of apprehension by the graduates in theorical-pratical questions that are essential to a competent professional performance. We realize that the conservative look and make of the social worker has not yet been overcome, and furthermore, has gained ground in their professional fields. This research indicate that among the factors that are presented as difficulties to the overcome of the fallacy that theory and practice are dissociated, is the formative process itself that still didn't get to break with the conservative rancidity of a baking education, and on the other side, the student profile itself that comes to the university with ethical, moral and cultural concepts and values previously established. We emphasize that among the factors that difficult the formative process and that influence professionals to assume a non-critical professional attitude or little reflective, that generates a gap between theory and practice: the living conditions, the established social relations, the form of apprehension in the society in general and inside the work field of the social workers, as well as the work conditions itself of these professionals.